Фантомная боль: [роман] / Олег Рой - Рой Олег (Капризы и странности судьбы, 2017)
Экземпляры: Чит. зал (20230619) / Инвентарный номер: 49885 / Цена: 178. 00 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Р 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44